Antibiotic prescribing in an intensive care unit: findings from a public Malaysian setting - Rozali, Mohammad Azrai; Ab Rahman, Norny Syafinaz; Sulaiman, Helmi; Abd Rahman, Nurul; Atiya, Nadia; Wan Mat, Wan Rahiza; Jamaluddin, Mohd Fadhil; Mazlan, Muhd Zulfakar; Mat Nor, Mohd Basri; Abdul Aziz, Mohd Hafiz; Hasan, Mohd Shahnaz (Wolters Kluwer India Pvt Ltd, 2020)
Introduction: Data on antibiotic prescribing together with its knowledge and perception in Malaysian ICU is lacking. Objectives: To explore knowledge, perception, and antibiotic prescribing among specialists and advanced trainees in Malaysian ICU. Materials and Methods: A cross-sectional survey was employed which consisted of three sections namely knowledge, perception, and practice. Three case vignettes consisted of hospital-acquired pneumonia (HAP), infected necrotising pancreatitis (INP), and catheter-related bloodstream infection (CRBSI) were presented in the practice section to gather information on prescribing practice. Results: About 868 respondents were approached but only 104 responded (12.0% response rate). Seven different classes of antibiotics giving a total of 390 were empirically prescribed for the three cases combined. Antibiotic prescribing compliance which indicates correct choice of antibiotics and dosing were 66.3%, 56.7%, and 19.2% for HAI, INP, and CRBSI respectively. In perception, 97.2% and 85.6% of respondents conceded that antibiotic concentration is inadequate, and that dosing be based on MIC respectively. Majority (94.2%) perceived that antibiotic dosing follows PK/PD profile but only half (50.9%) agreed that therapeutic drug monitoring be routinely performed. Comprehension on antibiotics showed that all respondents acknowledged PK/PD profile of antibiotics but only 64.4% able to correlate given antibiotic with their respective PK/PD. Only 13.5% of respondents able to identify the best PD approach for Î-lactam antibiotics in sepsis patients. Conclusion: Antibiotic prescribing was somewhat appropriate in Malaysian ICU. Prolong therapy and inadequate coverage are the hallmark need to be considered especially in CRBSI. Clinicians are conversant with available antibiotics but apprehension in its PK/PD is scant